Removal of a cannabis metabolite from human urine in microbial fuel cells generating electricity - Ozdemir, Murat; Enisoglu-Atalay, Vildan; Bermek, Hakan; Ozilhan, Selma; Tarhan, Nevzat; Catal, Tunc (Elsevier BV, 2019)
Abstract Electricity was generated directly from synthetic or human urine containing 11‑nor‑9‑carboxy‑Δ9‑tetrahydrocannabinol in air-cathode microbial fuel cells. Synthetic urine contained sodium acetate as carbon source, while actual human urine was used neat, without further supplements. Microbial fuel cells were capable of degrading more than 60% of the cannabis metabolite from human urine, while generating electricity. With synthetic urine, voltage generation reached 0.33 V, however the addition of 300 ng/mL of 11‑nor‑9‑carboxy‑Δ9‑tetrahydrocannabinol decreased the peak voltage to 0.27 V. This loss in power generation was nevertheless reversible when 11‑nor‑9‑carboxy‑Δ9‑tetrahydrocannabinol was removed from the media. Human urine containing 170 ng/mL 11‑nor‑9‑carboxy‑Δ9‑tetrahydrocannabinol produced 0.23 V of continuous electricity in the microbial fuel cells. The mechanism for degradation of cannabis metabolites in microbial fuel cells was discussed according to the results of the computational studies. In conclusion, wastewaters contaminated with a urine-based cannabis major metabolite could be treated in microbial fuel cells along with voltage generation as added-value.